WILAYAT AL-FAQIH SEBUAH KONSEP PEMERINTAHAN TEO-DEMOKRASI - Al-Walid, Kholid (Jurnal Review Politik, 2013)
The political system of wilayatul faqih was a new scientific discourse in the political world of Islam. This research seeks to explore the meaning of wilayatul faqih, as well as its association with the concept of theo-democracy. The findings of this study indicate that wilayatul faqih was the highest leadership held by a jurist who has qualified to lead the community in a country (Iran) during the period of Imam al-Mahdi raptures.Wilayatul faqih principle associated with awareness of the possibility of absolutism of a faqih. Therefore, the system wilayatul faqih in Iran coupled with the republican system. The incorporation of the systems led to a theo-democratic form of government. Thus, although the system wilayatul faqih implement the teachings of the Lord, which may have occurred errors and irregularities, but there are assemblies faqih that contains the scholars and intellectuals in charge of selecting and overseeing the performance of and policy faqih.